P1508A single center analysis of a 10-year period of lead removal. (18th June 2020) - Marinheiro, R; Neves, J P; Morgado, F; Carmo, P; Cavaco, D; Abecassis, M; Madeira, M; Magro, P; Braga, A; Marques, M; Boshoff, S; Calquinha, J; et al.
Abstract: BACKGROUND: The number of lead removal of cardiac implantable electronic devices (CIED) has increased in recent years. The recent European registry (ELECTRa) did not include all European centers and not all lead extractions are possible to be performed transvenously. AIMS: We aim to analyze all lead extraction procedures (transvenous or open surgery) performed in our center and the short- and long-term follow-up of these patients (pts). METHODS: We retrospectively reviewed all lead extractions performed from 2008 to 2017. We analyzed pts´ characteristics (personal history, cardiovascular risk factors, indication for device implantation, laboratory tests); indications for extraction; techniques used and personnel that participate in the procedure, complications peri- and post-procedural and short and long-term follow-up. RESULTS: A total of 189 pts (330 leads) were included (mean 69 ± 14 years, 73% male).  The follow-up was 54 (IQR 20-87) months. Median time after implant was 47 (IQR 19-98) months. Lead explant was performed in 30 patients (16%) and lead extraction (at least one lead implanted >1 year or a lead requiring assistance of specialized equipment) in 159 (84%). Indications for removal are presented in figure A. In those who were infected, isolation of the microorganism was possible in 35% and Staphylococcus aureus was the most common agent (51%). 101 procedures (53%) occurred in the operating room, while 89 (47%) were performed in the electrophysiology laboratory, but 47% of those with the participation of a surgeon. On the total, cardiac surgeons were responsible for 75% of the procedures. Removal was tried in 330 leads (98 atrium lead, 199 right ventricle lead (79 defibrillator lead) and 33 coronary sinus lead). Of those, 298 were completely removed, 14 were partially removed (<4cm of a lead remained in the patient body) and 18 were not removed (radiologic failure). On an individual patient basis, clinical success was achieved in 185 patients (97%). Techniques used in the 330 leads were distributed in figure B.  Surgical approach was necessary in 14 pts due to unsuccessful transvenous removal (n = 3), large vegetation in the lead (n = 4), concomitant valvular endocarditis (n = 2), other indication for open surgery (n = 4) and complicated transvenous removal (n = 1). Complications occurred in 6 patients: 3 persistent infections, 1 stroke, 2 vessel rupture. Related-procedural mortality was 1.5% (n = 3). The long-term survival of pts who performed open heart surgery was not different from those who underwent transvenous lead removal (logrank, p = 0.27) (figure C). CONCLUSION: Although being a low volume center (19 procedures/year) and including pts with transvenous and open surgery, lead removal was associated with a high success rate with low all cause complication and mortality rates. Emergent surgery due to acute complications was very rare (0.5%) and open heart surgery was mostly programmed and not associated with a worse outcome.